2014
DOI: 10.2337/dc14-0016
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Striatum, but Not Cortical Volume Loss, Is Related to Cognitive Dysfunction in Type 1 Diabetic Patients With and Without Microangiopathy

Abstract: OBJECTIVEPatients with longstanding type 1 diabetes may develop microangiopathy due to high cumulative glucose exposure. Also, chronic hyperglycemia is related to cerebral alterations and cognitive dysfunction. Whether the presence of microangiopathy is conditional to the development of hyperglycemia-related cerebral compromise is unclear. Since subcortical, rather than cortical, volume loss was previously related to cognitive dysfunction in other populations, we measured these brain correlates and cognitive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 36 publications
5
29
2
Order By: Relevance
“…In our study, we have previously shown that T1DM patients with proliferative retinopathy showed decrements in cognitive functions depending on processing speed and attention in comparison with controls and their counterparts with uncomplicated T1DM, and decreased processing speed in patients without proliferative retinopathy relative to controls [Van Duinkerken et al, ]. Although we did not demonstrate any alterations in cortical thickness, we did show lower subcortical gray matter volume in the thalamus, nucleus accumbens, putamen, and caudate nucleus [Van Duinkerken et al, ]. Both patients with and without proliferative retinopathy showed these alterations, albeit the effect size was largest in the group with retinopathy.…”
Section: Introductioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In our study, we have previously shown that T1DM patients with proliferative retinopathy showed decrements in cognitive functions depending on processing speed and attention in comparison with controls and their counterparts with uncomplicated T1DM, and decreased processing speed in patients without proliferative retinopathy relative to controls [Van Duinkerken et al, ]. Although we did not demonstrate any alterations in cortical thickness, we did show lower subcortical gray matter volume in the thalamus, nucleus accumbens, putamen, and caudate nucleus [Van Duinkerken et al, ]. Both patients with and without proliferative retinopathy showed these alterations, albeit the effect size was largest in the group with retinopathy.…”
Section: Introductioncontrasting
confidence: 48%
“…Based on the results of our previous RSN connectivity analysis, alterations were hypothesized strongest in patients without proliferative retinopathy. Next, in all patients, we aimed at identifying the relationship between potential alterations in ECM and degree centrality and previously observed cognitive decrements, altered RSN functional connectivity, and lower subcortical volume [Van Duinkerken et al, ]. To this end, we correlated ECM and degree centrality values with cognitive performance on the domains of general cognitive ability, information processing speed, and attention.…”
Section: Introductionmentioning
confidence: 99%
“…The putamen (and the basal ganglia collectively) has been shown to be selectively injured in a number of diseases, with volume regional loss reported in Type 1 Diabetes [14], multiple sclerosis [15], and Alzheimer’s disease [16]. The mechanistic relationships between these conditions and HIV may be potentially related to inflammation or vascular injury, and warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…61, 77-80 Many studies have established associations between diabetic cognitive dysfunction and progressive damage to brain structure, including increased cortical atrophy, microstructural abnormalities in white matter tracts, atrophy of the striatum (in type 1) and hippocampus (in type 2), and gray matter loss. 81-85 At the moment, it is not clear how diabetes causes these structural losses in the brain, given that the brain and its microvasculature are not easily accessible in vivo . 86, 87 The Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications (DCCT/EDIC) refuted the hypothesis that severe hypoglycemia caused cognitive dysfunction.…”
Section: Relationship Between Diabetic Retinal Neurodegeneration and mentioning
confidence: 99%
“…79 Several studies have shown an association between structural changes from diabetes in the brain and retinal microvasculopathy. 81, 88-91 Some authors therefore claim that the functional and structural changes in the brain induced by diabetes are primarily caused by microvasculopathy. 78, 88, 90, 92, 93 Other authors, however, claim that neuropathy results directly from hyperglycemia 86 or from frequent oscillations in serum glucose levels, 94 resulting in cognitive decline.…”
Section: Relationship Between Diabetic Retinal Neurodegeneration and mentioning
confidence: 99%